Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn212
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Rhythms

Abstract: It is increasingly evident that brain function involves oscillatory activity in various frequency bands. This realization encouraged psychologists to consider that perception and cognition may operate periodically, as a succession of cycles mirroring the underlying oscillatory cycles. This idea, related to the age‐old notion of discrete perception, has resurfaced in recent years, fueled by advances in neuroscientific techniques. Contrary to earlier views of discrete perception as a unitary sampling rhythm affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 215 publications
1
27
0
2
Order By: Relevance
“…Across trials, behavioral performance (e.g., target detection rate) then varies over time since cue onset in a rhythmic fashion at frequencies in the theta and alpha ranges (approx. 4-12 Hz) (VanRullen, 2016b). These fluctuations of performance strongly contradict the long held assumption of continuous attentional processing, which would predict constant or increasing performance with time since cue onset.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Across trials, behavioral performance (e.g., target detection rate) then varies over time since cue onset in a rhythmic fashion at frequencies in the theta and alpha ranges (approx. 4-12 Hz) (VanRullen, 2016b). These fluctuations of performance strongly contradict the long held assumption of continuous attentional processing, which would predict constant or increasing performance with time since cue onset.…”
mentioning
confidence: 72%
“…It is a long-standing notion that the continuous stream of sensory information is sampled discretely by the perceptual system (VanRullen, 2016b). Recently, a series of psychophysical studies have demonstrated attentional sampling in tasks including visual target detection (Dugué et al, 2015;Landau & Fries, 2012;VanRullen et al, 2007), discrimination (Song et al, 2014), and priming (Huang et al, 2015), as well as auditory target discrimination (Ho et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, accumulating evidence has demonstrated the predictive nature of the spectral components of ongoing oscillations (i.e., phase and amplitude) on perceptual processes (VanRullen et al, 2011; VanRullen, 2016, in press). Interestingly, TMS, and in particular spTMS due to its high temporal and spatial resolution compared with other stimulation techniques such as tACS/tDCS (Paus et al, 2001; Miniussi et al, 2013), can be used to characterize spontaneous activity and its role on perceptual processes.…”
Section: Tms To Probe Intrinsic Rhythmicity Of Perception and Attentionmentioning
confidence: 99%
“…Recently, in a comprehensive review of the oscillation literature, VanRullen reported that two types of perceptual rhythms can coexist in the visual domain: an alpha rhythm (~10 Hz) that would be associated with sensory processes, and a theta rhythm (~7 Hz) that would be associated with attentional sampling (VanRullen, 2016, in press). spTMS studies reported in the previous section offer to extend this observation.…”
Section: A Tentative Model Of the Role Of Alpha And Theta Oscillationmentioning
confidence: 99%
See 1 more Smart Citation